The concept «People» in the poetic discourse of «Kobzar» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The features of the manifestation and functioning of one of the main concepts «Kobzar’s» MegaText are examined. We investigate the nature of the formation of evaluation and expressive emotive component of conceptual content.
Keywords: concept; conceptual; MegaText; evaluation; atributiv